1991
DOI: 10.1007/bf00161664
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation from organic molecules incorporated in sol-gel matrices

Abstract: Orientation of optically nonlinear organic molecules inside sol-gel matrices upon application of an external D.C. electrical field is demonstrated for the first time. The quadratic nonlinear response of silicon oxide or transition metal oxide based gels containing organic molecules has been determined from Electric Field Induced Second Harmonic (EFISH) measurements. Large concentrations of Optically Nonlinear Organic Molecules (ONOM) have been either incorporated inside the macromolecular network or chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 33 publications
1
16
1
2
Order By: Relevance
“…Intercalation provides an alternative to sol-gel methods (28), at least in certain circumstances, for the synthesis of hybrid organic-inorganic nanocomposites, providing the advantage of a better crystallinity that can be im~ortant when coouerative interactions are reiuired. We did not' record any sigruficant decay of the NLO signal over a period of several months, which is a crucial point in the search for suitable SHG materials.…”
Section: \ mentioning
confidence: 99%
“…Intercalation provides an alternative to sol-gel methods (28), at least in certain circumstances, for the synthesis of hybrid organic-inorganic nanocomposites, providing the advantage of a better crystallinity that can be im~ortant when coouerative interactions are reiuired. We did not' record any sigruficant decay of the NLO signal over a period of several months, which is a crucial point in the search for suitable SHG materials.…”
Section: \ mentioning
confidence: 99%
“…[46,271] In the sol-gel process, two approaches are commonly proposed, either simple dispersion with low energy coupling (Class I) or covalent bonding with strong coupling (Class II), the latest being often mentioned as the most stable one. Since the very precursor works in the early 90's when was demonstrated the efficient doping and orientation of dyes in inorganic matrices, [272] large number of reports explored the capacity of sol-gel matrices to stabilize the orientation of chromophores. Large second order optical nonlinearities were observed using covalent grafting of the dyes to the silica backbone.…”
Section: Dye-doped Inorganic Matricesmentioning
confidence: 99%
“…Studies of the dopant dynamics of a tetramethoxysilane (TMOS)/dimethylaminopyridine (DMAP) sol ± gel have shown that the sol phase is characterized by an increase in length of polymers with time which results in an increasing viscosity of the medium. [15] Macroscopic gelation occurs when the longer polymer species are consumed to form the long-distance network. This process results in a temporary decrease in hindrance (local viscosity) around dopant molecules and b-carotene experiences a sudden return to a solventlike environment.…”
Section: Visualization Of Surface Gelation Processes In a Doped Sol ±mentioning
confidence: 99%